Musculoskeletal radiology training in the UK: a national survey by the British Society of Skeletal Radiologists. Issue 9 (September 2021) - Dalili, D.; Mackay, J.; Robinson, P.; Mansour, R.; ,
Abstract : AIM: To identify the standard of core and subspecialist musculoskeletal (MSK) training across deaneries in the UK. MATERIALS AND METHODS: An online survey of 46 questions with responses in Likert scale or dichotomous formats was distributed to members of the Society of Radiologists in training, British Society of Skeletal Radiologists (BSSR), Training Programme Directors and the Royal College of Radiologists (RCR) Junior Radiology Forum representatives for national training schemes across the country. Responses were analysed descriptively with narrative analysis of free-text comments. RESULTS: One hundred and seventy-eight participants completed the survey. Forty-six percent (81/178) were core trainees (ST1–3), 47% (84/178) were subspecialist trainees, and 7% (13/178) were newly qualified consultants (<2 years in post). All (178/178) of the participants had a dedicated MSK rotation, with a duration of ≥3 months in 76% (136/178). Only one-third received a dedicated period in MSK ultrasound and only 60% (107/178) had been actively involved in interventional procedures during their training. Overall, 21% (37/178) and 42% (75/178) of participants rated the quality of their MSK training as excellent and good, respectively. The majority (93%, 168/178) thought that MSK training could be improved, especially for ultrasound (62%, 110/178) and interventional computed tomography (CT) or fluoroscopy (57%, 101/178). CONCLUSIONS: There are inconsistencies in MSK training offered in the UK. Although the majority of trainees are satisfied, there were gaps and potential threats to the quality of training. MSK training is witnessing substantial demand from trainees and workforce strategists necessitating tactical investments to standardise and enhance its quality. Highlights: Core MSK radiology training remains widely variable across the UK. 50% of core and 86% subspecialty trainees are satisfied with current exposure. 20% of core trainees report lack of US sessions or < 4 hours of weekly US in 56%. 95.5% core and all subspecialist trainees believe MSK training could be improved. Other healthcare professionals competing for US experience may impact training.